-5n+9+7n=7n-8n-9

Simple and best practice solution for -5n+9+7n=7n-8n-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5n+9+7n=7n-8n-9 equation:


Simplifying
-5n + 9 + 7n = 7n + -8n + -9

Reorder the terms:
9 + -5n + 7n = 7n + -8n + -9

Combine like terms: -5n + 7n = 2n
9 + 2n = 7n + -8n + -9

Reorder the terms:
9 + 2n = -9 + 7n + -8n

Combine like terms: 7n + -8n = -1n
9 + 2n = -9 + -1n

Solving
9 + 2n = -9 + -1n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add 'n' to each side of the equation.
9 + 2n + n = -9 + -1n + n

Combine like terms: 2n + n = 3n
9 + 3n = -9 + -1n + n

Combine like terms: -1n + n = 0
9 + 3n = -9 + 0
9 + 3n = -9

Add '-9' to each side of the equation.
9 + -9 + 3n = -9 + -9

Combine like terms: 9 + -9 = 0
0 + 3n = -9 + -9
3n = -9 + -9

Combine like terms: -9 + -9 = -18
3n = -18

Divide each side by '3'.
n = -6

Simplifying
n = -6

See similar equations:

| 8+13x=216 | | 1/5 | | 4x-17=2x+4 | | f(x)=8cosx | | -4y-9=6y+11 | | -2x^2-x=20 | | 11/2X=10 | | X^2+2x+4=3 | | 3(x+5)+2x=5x-15 | | 6x+7x+8=540 | | x^2-(m+1)*x+m=0 | | x^5-7x^3+9x=-x | | 6x+7x+8=360 | | x/187 | | (8,3)x= | | 3(10+x)=3 | | 6x+7x+8=36 | | x-41=-6 | | 12x-3-2x=0 | | 6/7a=16 | | 6x+3-9x=12-15x+12x-9 | | 4a^2+12a-27=0 | | (2/3)x=-9 | | 1/3d(60-t) | | -2(-7+3x)=-22 | | 3(2c-1)-2=2c+3 | | 6(10-3x)=10-8x | | m-20=10 | | 3/14N=3/16 | | (4t+5)(3t+10)=0 | | -8+3x=-4x+55 | | -2(x+1)+x=7-4x |

Equations solver categories